2010
DOI: 10.1111/j.1600-0560.2009.01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Testicular choriocarcinoma metastatic to skin and multiple organs. Two case reports and review of literature

Abstract: Two cases of males with subcutaneous masses as the first clinical sign of testicular choriocarcinoma are reported. The urine and serum human chorionic gonadotropin (hCG) test confirmed high level hCG from male choriocarcinoma. These cases, although very rare, can be a great diagnostic and therapeutic challenge and should be considered in the differential diagnosis of subcutaneous masses occurring in young males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In few previously reported cases of testicular GCT with histologically multiorgan metastases by CC, the primary tumor also contained other components of A B C D GCT. [11][12][13][14] All CCs in this series, whether pure or predominant, presented with markedly high levels of serum b-hCG, mostly in the 100,000s range. Prior studies had shown that an elevated level of serum b-hCG, particularly >50,000 IU/L, is an independent indicator of poor outcome in testicular GCT.…”
Section: Discussionmentioning
confidence: 96%
“…In few previously reported cases of testicular GCT with histologically multiorgan metastases by CC, the primary tumor also contained other components of A B C D GCT. [11][12][13][14] All CCs in this series, whether pure or predominant, presented with markedly high levels of serum b-hCG, mostly in the 100,000s range. Prior studies had shown that an elevated level of serum b-hCG, particularly >50,000 IU/L, is an independent indicator of poor outcome in testicular GCT.…”
Section: Discussionmentioning
confidence: 96%
“…6 Choriocarcinomas are rare and may originate from fetal trophoblasts or germ cells in the testes or ovaries. They account for about 1% of all testicular carcinomas.…”
Section: Questions For Considerationmentioning
confidence: 99%
“…Unlike other GCTs, choriocarcinomas metastasize early, spreading hematogenously to other sites, most often lung, liver, and brain. 6 Half of patients will have metastatic disease at the time of presentation. 2 Metastases have been reported in as many as 83% of patients, with most patients having multiple sites of metastases.…”
Section: Discussionmentioning
confidence: 99%